Evaluation of MPC-based arctan droop control strategy in islanded microgrid - Iyakaremye, J.D.D.; Nyakoe, G.N.; Wekesa, C.W. (EAI Endorsed Transactions on Energy Web, 2021)
The microgrid (MG) is an emerging technology for supplying energy from renewable energy sources (RES). Due to their intermittent nature, RES require an inverter and smooth operation control system when integrated into an MG. Conventional droop control is commonly used in microgrid control but cannot achieve adequate power-sharing when output impedances of inverters are different; thus, enhancing its performance is required. This paper’s main objective is to design a finite control set model predictive control (FSC-MPC) based arctan droop control and evaluate its performance against the conventional droop control strategy. The proposed control technique guarantees a strong transient response when there is a dynamic load change during MG operation. The results showed that the proposed control strategy ensures proportionate power-sharing of paralleled voltage source inverters with unequal line impedances than the traditional droop controller, which can vary.
Keywords: Arctan droop control; model predictive control; power-sharing; comparative evaluation; microgrid